Antibiogram of bacteria isolated from cervico-vaginal discharge of endometritic cows in Himachal Pradesh - KUMAR, PRAVESH; SINGH, MADHUMEET; SHARMA, AKSHAY (The Indian Journal of Animal Sciences, 2018)
The present study was designed to assess the antibiotic sensitivity pattern of different bacterial flora isolated from 120 cervico-vaginal mucus (CVM) samples which were collected from cows suffering from endometritis. Out of 120 discharge samples, 105 exhibited bacterial growth and 15 samples were bereft of bacteria in nutrient broth. The in vitro antibiotic sensitivity test for each turbid sample was done by disc diffusion method. Antibiotics used were ciprofloxacin (Cx), enrofloxacin (Ex), gentamicin (G), ofloxacin (Of), ampicillin (Am), oxytetracycline (O), co-trimoxazole (Co), tetracycline (T), penicillin (P) and metronidazole (Mt). Highest sensitivity was recorded for ciprofloxacin followed by enrofloxacin and ofloxacin, whereas, highest resistance was recorded for penicillin followed by metronidazole and tetracycline. The antibiogram could be useful to the practitioners in choosing the most efficient antiibacterial products.